Publication by Grace - Redmeh, Paul C. (Methods of Information in Medicine, 1965)
GRACE (Graphic Arts Composing Equipment) is a computer photatypesetter used in MEDLARS, a bibliographic publication and retrieval system in operation at the National Library of Medicine in Bethesda, Maryland. MEDLARS objectives in the publication of Index Medicus and other bibliographies required the development of new high speed electronic and opTficSF’equipment to expose film copy for printing. The characteristics and limitations of the GRACE equipment are described in this article. Computer programs and operating procedures used in the production of MEDLARS publications by GRACE are discussed. Operational experience demonstrates that GRACE is a successful application of computer technology to bibliographic publication.